Do children with supraventricular tachycardia treated with ablation therapy have similar quality of life as healthy children? - Szafran, Emilia; Baszko, Artur; Bukowska-Posadzy, Anna; Łaźniak, Agata; Moszura, Tomasz; Siwińska, Aldona; Walkowiak, Jarosław; Bobkowski, Waldemar (Journal of Medical Science, 2017)
Introduction. There are a few available studies evaluating quality of life (QoL) in pediatric patients with supraventricular tachycardia (SVT) treated with ablation but they are based on small groups of patients. The aim of the paper was to compare the QoL in children with SVT treated with successful ablation with the group of healthy children.Materials and Methods. The study included 122 SVT children who underwent a successful ablation therapy and 83 healthy children. The Qol was assessed, using the WHOQOL-BREF and the Pediatric Arrhythmia Related Score (PARS) - a specific questionnaire developed by the authors, related to patients' own feelings and observations concerning arrhythmia.Results. On the basis of WHOQOL-BREF no significant differences were found in all the measured domains. On the basis of PARS in SVT-group the patients still reported significantly increased symptoms within physical domain in comparison with the healthy group (1.8 ± 0.5 vs 1.6 ± 0.3; p = 0.0195) as well as increased negative feelings within psychological domain (2.3 ± 0.7 vs 2.1 ± 0.6; p= 0.0172). Conclusions. On the basis of the general questionnaire all scores in SVT group are comparable with healthy children. When analyzing PARS questionnaire six months after the ablation procedure the physical and psychological functioning of SVT children was still worse than in the group of healthy children. On the basis of the performed analysis we believe that PARS questionnaire is a more useful and sensitive tool than WHOQOL-BREF when evaluating ablation influence on patients’ QoL.
Keywords: arrhythmia; pediatric; quality of life